(untitled) (Journal of University of Babylon for Engineering Sciences, 2023)
In today’s world, ADDITIVE MANUFACTURING (AM) is a well-known method for creating true three-dimensional objects, either out of metals, ceramics, plastics, or a combination of these materials. ADDITIVE MANUFACTURING (AM) is connected with a series of rapid heating and cooling cycles, as well as substantial temperature gradients, which result in the development of complicated thermal histories, which have a direct impact on the resulting microstructures. Due to the nature of this dynamic and far-from-equilibrium process, different microstructural features emerge. For instance, these are likely to induce changes in the corrosion characteristics of ADDITIVE MANUFACTURING (AM) stainless steels, which have superior mechanical properties and corrosion resistance when manufactured using other production methods. Because such modifications are not fully understood at this time, inconsistencies and conflicts in the literature on the corrosion behaviour of ADDITIVE MANUFACTURING (AM) stainless steels are regularly seen. The preparation and characterization of additively made stainless steel is the subject of this work, which provides a critical assessment. In terms of producing huge metallic structures at high deposition rates and cheap costs, WIRE ARC ADDITIVE MANUFACTURING (WAAM) has emerged as a viable method. This article reviews some ADDITIVE MANUFACTURING (AM) methods used mostly with metallic materials focusing on the WIRE ARC ADDITIVE MANUFACTURING (WAAM) of stainless steel.